2009
DOI: 10.1039/b912669d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular water-oxidation catalysts for photoelectrochemical cells

Abstract: Photoelectrochemical cells that efficiently split water into oxygen and hydrogen, "the fuel of the future", need to combine robust water oxidation catalysts at the anode (2H(2)O -> O-2 + 4H(+) + 4e(-)) with hydrogen reduction catalysts at the cathode (2H(+) + 2e(-) -> H-2). Both sets of catalysts will, ideally, operate at low overpotentials and employ light-driven or light-assisted processes. In this Perspective article, we focus on significant efforts to develop solid state materials and molecular coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
111
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(114 citation statements)
references
References 77 publications
1
111
0
2
Order By: Relevance
“…Indeed, even the oxygen evolving complex of photosystem II experiences up to a ten-fold reduction in catalytic activity in vivo as opposed to in vitro. 340,341 In addition, Bard et al 350 have noted that the heterogeneous electrochemical rate constants for reactants bound in a surface layer are generally 2-3 orders of magnitude smaller than those for the same reactants in the solution phase. In light of this, a direct comparison between surface based and solution based catalysts seems unreasonable.…”
Section: Electrocatalytic Performance -Turnover Frequenciesmentioning
confidence: 99%
“…Indeed, even the oxygen evolving complex of photosystem II experiences up to a ten-fold reduction in catalytic activity in vivo as opposed to in vitro. 340,341 In addition, Bard et al 350 have noted that the heterogeneous electrochemical rate constants for reactants bound in a surface layer are generally 2-3 orders of magnitude smaller than those for the same reactants in the solution phase. In light of this, a direct comparison between surface based and solution based catalysts seems unreasonable.…”
Section: Electrocatalytic Performance -Turnover Frequenciesmentioning
confidence: 99%
“…[15,16] Of these catalysts only a few have been successfully attached to electrode surfaces, which is a prerequisite for their incorporation into photoelectrochemical devices. [17] To the best of our knowledge there are no reports of the successful integration of these types of water oxidation catalysts with a solar cell into a tandem water-splitting device. [17] We recently reported that a tetranuclear Mn-oxo cluster, [Mn 4 O 4 L 6 ] + (1 + ; L= (p-Me-C 6 H 4 ) 2 PO 2 ; Scheme 1 A), [18,19] is able to catalyze the oxidation of water for extended periods when doped within the proton-conducting channels of a Nafion membrane, polarized at 1 V (vs Ag/AgCl) and illuminated with visible light.…”
mentioning
confidence: 98%
“…Considerable efforts have been made to develop synthetic analogues of the oxygen-evolving complex (OEC) in photosystem II (PSII), which contains a Mn 4 Ca cluster as the water oxidation catalyst. [2] These model systems have mainly been focused either on manganese-based complexes, [3][4][5][6][7] which mimics natures preference, or on ruthenium-based complexes, although other metal complexes (Co, Ir, Fe) have also been investigated. [25][26][27][28][29] Although only a very few of the manganese complexes that have been synthesised have shown moderate to low catalytic activity for water oxidation, [30][31][32][33][34] many ruthenium complexes with high catalytic activities have been developed.…”
Section: Introductionmentioning
confidence: 99%